2019
DOI: 10.3389/fonc.2019.00217
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Multicenter Study of Gantry-Based Stereotactic Radiotherapy Boost for Intermediate and High Risk Prostate Cancer (PROMETHEUS)

Abstract: Objectives: To report feasibility, early toxicity, and PSA kinetics following gantry-based, stereotactic radiotherapy (SBRT) boost within a prospective, phase 2, multicenter study (PROMETHEUS: ACTRN12615000223538). Methods: Patients were treated with gantry-based SBRT, 19–20 Gy in two fractions delivered 1 week apart, followed by conventionally fractionated IMRT (46 Gy in 23 fractions). The study mandated MRI fusion for RT planning, rectal displacement, and intrafraction imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…According to the IPSS questionnaire, 27% of patients had mild symptoms with an average score of 5 (range, 4-6), and the majority of patients (62%) demonstrated moderate symptoms with an average score of 12.8 (range, [8][9][10][11][12][13][14][15][16][17][18][19]. There was no statistically significant difference between 18 Gy and 21 Gy arms, except in baseline quality of life, which included more patients who answered "delighted" in 18 Gy arm. Figure 2 demonstrates changes in symptom scores at 5-time points (baseline, after WPRT, after CyberKnife boost, 1 month after radiotherapy, and 4 months after radiotherapy) in 25 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the IPSS questionnaire, 27% of patients had mild symptoms with an average score of 5 (range, 4-6), and the majority of patients (62%) demonstrated moderate symptoms with an average score of 12.8 (range, [8][9][10][11][12][13][14][15][16][17][18][19]. There was no statistically significant difference between 18 Gy and 21 Gy arms, except in baseline quality of life, which included more patients who answered "delighted" in 18 Gy arm. Figure 2 demonstrates changes in symptom scores at 5-time points (baseline, after WPRT, after CyberKnife boost, 1 month after radiotherapy, and 4 months after radiotherapy) in 25 patients.…”
Section: Resultsmentioning
confidence: 99%
“…HDRB might be replaced by EBRT while retaining its high-dose-rate effect. Pryor et al [18] evaluated a gantry-based linear accelerator for SBRT boost and reported a 2-year cumulative incidence of grade 2 or more GU toxicities of 24.9%. This result was slightly higher than that reported by other studies, except Anwar et al [9], which reported a rate of 1.4-14% (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several other factors may have also contributed to the low GI toxicity scores, such as the use of coplanar arc therapy 390 Joseph Drabble and Heather Drury-Smith with flattening free filter dose delivery, reduced posterior PTV margins and intra-fraction imaging verification of fiducial markers using exactrac®. 16 Conclusion HS has been shown to reduce rectal planning doses in radical prostate radiotherapy. There is a correlation between placement symmetry and reduced rectal dose.…”
Section: High-risk Patientsmentioning
confidence: 97%
“…For patients with high-risk prostate cancer, treatment options most often include surgery or a combination of androgen deprivation therapy (ADT) and radiation therapy. External beam radiation therapy (EBRT) is the most common method to deliver radiotherapy for localized prostate cancer.Multiple studies have demonstrated that dose-escalated external beam radiation therapy (DE-EBRT) improves local control, freedom from biochemical failure, freedom from distance metastases, and decreases the need for salvage therapy (3)(4)(5)(6). DE-EBRT, however, has also been associated with increases in late genitourinary (GU) and gastrointestinal (GI) toxicities (3).…”
Section: Introductionmentioning
confidence: 99%